2013
DOI: 10.1128/mbio.00419-13
|View full text |Cite
|
Sign up to set email alerts
|

SuhB Is a Regulator of Multiple Virulence Genes and Essential for Pathogenesis of Pseudomonas aeruginosa

Abstract: During initial colonization and chronic infection, pathogenic bacteria encounter distinct host environments. Adjusting gene expression accordingly is essential for the pathogenesis. Pseudomonas aeruginosa has evolved complicated regulatory networks to regulate different sets of virulence factors to facilitate colonization and persistence. The type III secretion system (T3SS) and motility are associated with acute infections, while biofilm formation and the type VI secretion system (T6SS) are associated with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 48 publications
(62 reference statements)
4
86
0
Order By: Relevance
“…36 Other stress-related genes include the small regulatory RNA genes rsmY and rsmZ, the expression of which are essential to enhance population density under environmental stress, 37 and also for biofilm formation. 38 In this study, we observed a significantly reduced expression of the rsmZ gene in AgCNT-treated samples and an upregulation in gentamicin-treated samples. A study has shown that upregulation of these regulatory RNAs resulted in more biofilm formation, by increasing expression of the QS gene lasR.…”
Section: Discussionmentioning
confidence: 52%
“…36 Other stress-related genes include the small regulatory RNA genes rsmY and rsmZ, the expression of which are essential to enhance population density under environmental stress, 37 and also for biofilm formation. 38 In this study, we observed a significantly reduced expression of the rsmZ gene in AgCNT-treated samples and an upregulation in gentamicin-treated samples. A study has shown that upregulation of these regulatory RNAs resulted in more biofilm formation, by increasing expression of the QS gene lasR.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, SuhB may control the rates of peptide chain elongation and protein folding [42]. In contrast, the SuhB homolog of P. aeruginosa plays an important role in pathogenesis to control the genes required for acute and chronic infection [47]. Burkholderia cepacia SuhB is required for the secretion of proteins associated with motility and biofilm formation [48], suggesting that the physiological functions of SuhB homologs are complex, which may be true for B. subtilis YktC.…”
Section: Discussionmentioning
confidence: 99%
“…It seems plausible that the ribosomal access to this region could be enhanced by DeaD. In addition to DeaD, RsmA also stimulates ExsA synthesis at a posttranscriptional level (23,46). Whether DeaD and RsmA activities function independently or are dependent upon one another will be the subject of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The remainder of this study focuses on gene PA2840, identified by two independent transposon insertion events (Table 2) and recently identified in another mutagenesis screen for regulators of T3SS gene expression (46). PA2840, referred to here as deaD, encodes a homolog of Escherichia coli DeaD and is annotated as a probable ATP-dependent RNA helicase (47).…”
Section: Identification Of Novel Extrinsic Regulators Of T3ss Gene Exmentioning
confidence: 99%